2012
DOI: 10.1152/ajpcell.00298.2011
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle regeneration is delayed by reduction in Xin expression: consequence of impaired satellite cell activation?

Abstract: Xin is a striated muscle-specific actin-binding protein whose mRNA expression has been observed in damaged skeletal muscle. Here we demonstrate increased Xin protein expression early postinjury (≤ 12 h) and localization primarily to the periphery of damaged myofibers. At 1 day postinjury, Xin is colocalized with MyoD, confirming expression in activated satellite cells (SCs). By 5 days postinjury, Xin is evident in newly regenerated myofibers, with a return to preinjury levels by 14 days of regeneration. To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Finally, larger myotubes were formed in the regenerating regions at day 14 after CTX injection, suggesting that the skeletal muscle injury caused by CTX was repaired. In agreement with these results, the expression level of myogenic nuclear factor myoD, which has an important role in the proliferation of satellite cells in an adult skeletal muscle, increased after CTX injection as described previously 15,19) (Fig. 1B).…”
Section: Resultssupporting
confidence: 91%
“…Finally, larger myotubes were formed in the regenerating regions at day 14 after CTX injection, suggesting that the skeletal muscle injury caused by CTX was repaired. In agreement with these results, the expression level of myogenic nuclear factor myoD, which has an important role in the proliferation of satellite cells in an adult skeletal muscle, increased after CTX injection as described previously 15,19) (Fig. 1B).…”
Section: Resultssupporting
confidence: 91%
“…Single muscle fibers were obtained from Akita and WT mice at 12 weeks of age (8 weeks of diabetes) from the left and right extensor digitorum longus and peroneus muscles, as previously described (15). Fibers were fixed immediately after isolation (referred to as Control fibers) or placed in culture dishes with plating media (10% normal horse serum, 0.5% chick embryo extract in DMEM) overnight (18 h; referred to as Activated fibers).…”
Section: Single Muscle Fiber Isolationmentioning
confidence: 99%
“…SC activation was assessed in floating cultures by adding 10 mmol/L BrdU to the plating media and incubating newly isolated single fibers for 24 h. Fibers were fixed and stained for BrdU (Abcam, Cambridge, MA), as previously described (15). SCs that became activated and entered the cell cycle incorporated BrdU.…”
Section: Sc Activationmentioning
confidence: 99%
“…Previous studies have demonstrated that all of them are validated for use (Aguilera et al, 2011;Averous et al, 2012;Della Pietra et al, 2015;Dixon et al, 2011;Gong et al, 2015;Kim et al, 2011;Li et al, 2012;Murphy et al, 2011;Nissar et al, 2012;Rao et al, 2014;Sarkar and Zohn, 2012;Takeda et al, 2014;Tan et al, 2011;Taniguchi et al, 2011;Wu et al, 2010;Zhang et al, 2011).…”
Section: Antibodiesmentioning
confidence: 99%